Network analysis and site selection for cross-disciplinary collaboration: The Plant and Environmental Science Building at Michigan State University - Felichism Kabo (PLoS ONE, 2025)
Site selection is a complex, multicriteria process and a key if poorly understood contributor to the success of new scientific facilities. Typical site selection factors include the budget, sustainability, accessibility, utility and infrastructure costs, and environmental factors, e.g., air quality. Ideally, site selection should also reflect the organizational imperatives that drive the construction of new facilities in higher education, such as stimulating cross-disciplinary scientific collaboration. Traditional site selection is ill-equipped to account for the complex configurational effects of the built environment on cross-disciplinary scientific collaboration. Systems approaches, like network analysis, enable the simultaneous examination of a system (e.g., built environment) and its parts. This paper reports on a novel application of network analysis to examine the potential for site selection for cross-disciplinary collaboration for the Plant and Environmental Science Building (PESB) at Michigan State University (MSU). The network analysis of the two potential PESB sites, A and B, helped to identify which of the two sites is better configured to foster connections within PESB’s future research community. The results indicate site A’s paths are less deep on average and have more connections between other pairs of paths. Site A’s network is also more cohesive and less fragmented. Site A is thus better configured to support potential encounters and has a higher spatial legibility which correlates with better cognitive maps for individuals. These findings are all positively associated with collaboration. The study illustrates that network analysis can enable site selection that accounts for key organizational imperatives like cross-disciplinary collaboration.